Children Without Bruised Knees: Responding to Material and Ideational (Mis)alignments. Issue 5 (June 2018) - Raaijmakers, Aafke; Vermeulen, Patrick A.M.; Meeus, Marius T.H.
Institutional theorists have predominantly focused on the symbolic and cognitive side of institutions. So far, the role of materiality has been largely overlooked in institutional studies. Material aspects of organizing can nevertheless critically shape actors' responses to institutional pressures, not least because material and ideational aspects are often intermingled. In this paper, we extend Oliver's (1991) conceptual framework of strategic responses. We show how managers assess and compare the material and ideational aspects of new institutional requirements with their existing material and ideational situation and balance both aspects in their strategic responses. We find that the degree of (mis)alignment subsequently shaped their evaluation of the consequences of (non)conformity and the breadth of responses available to them. In fact, we find that the nature of institutional requirements – material versus ideational – actually restricts the range of strategic response options.